2016
DOI: 10.1021/acsami.5b11961
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fogging/Self-Healing Properties of Clay-Containing Transparent Nanocomposite Thin Films

Abstract: Highly transparent antifogging films were successfully prepared on various substrates, including glass slides, silicon, copper and PMMA, by spin-coating a mixture of polyvinylpyrrolidone and aminopropyl-functionalized, nanoscale clay platelets. The resulting films were superhydrophilic and showed more than 90% transmission of visible light, as well as excellent antifogging and self-healing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 31 publications
10
110
0
Order By: Relevance
“…This may lead to many problems for the use of eyeglasses, windows, mirrors, goggles, and optical instruments. [1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to many problems for the use of eyeglasses, windows, mirrors, goggles, and optical instruments. [1][2][3][4] Over the last few decades, an extensive research studies have been reported to prevent the formation of fog and frost on solid surfaces by different approaches including superhydrophobic coatings, 5-7 superhydrophilic coatings 8,9 and combinations of both hydrophilic and hydrophobic properties in the coating. [10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Hydrophilic surfaces that have a water contact angle of less than 5 o exhibit excellent anti-fog properties because they allow water droplets to spread uniformly to form a thin water film, which reduces light scattering. 9,16,17 In general, superhydrophilicity can be obtained by various chemical and physical methods. 18 One common approach is to coat hydrophilic inorganic nanoparticles such as SiO2 and TiO2.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing/healable materials with extended service life and enhanced reliability can significantly reduce raw material consumption and contribute in the realization of a sustainable society . Currently, endowing artificial materials with healing function is becoming an important consideration in material design.…”
Section: Summary Of Mechanical Properties Of the Paa–pvpon Compositesmentioning
confidence: 99%
“…The wetting behavior of solid and liquid surfaces has been studied extensively. Superhydrophilic surfaces (whose water droplet contact angle is <5° within 0.5 s) have attracted considerable attention due to their special properties and their broad range of applications in self‐cleaning, anti‐fogging, anti‐fouling, oil–water separation, anticorrosion, fog collection, and organic solar cells . To prepare superhydrophilic surfaces, a lot of effort has been devoted using different strategies, including TiO 2 ‐based coatings, etching, hydrothermal treatment and layer‐by‐layer assembly .…”
Section: Introductionmentioning
confidence: 99%
“…The wetting behavior of solid and liquid surfaces has been studied extensively. Superhydrophilic surfaces (whose water droplet contact angle is <5° within 0.5 s) have attracted considerable attention due to their special properties and their broad range of applications in self-cleaning, [1,2] anti-fogging, [3,4] anti-fouling, [5,6] oil-water separation, [7,8] anticorrosion, [9] fog www.advancedsciencenews.com www.mme-journal.de…”
Section: Introductionmentioning
confidence: 99%